Prevalence of persistent primary teeth at the East Selemadeg I Community Health Centre in Tabanan, Bali, from period January 2024 to March 2025: Prevalensi kasus persistensi gigi sulung di UPTD Puskesmas Selemadeg Timur I Tabanan Bali pada periode Januari 2024 hingga Maret 2025 - Molin, Ni Made; Pratama, I Wayan Agus Wirya; Kusumadewi, Ni Wayan Adi; Palguna, I Gede Pandu (Makassar Dental Journal, 2025)
Dental health problems can occur in all age groups, especially in children, and it is important to pay attention to them. In addi-tion to caries, another common dental problem in children is persistent primary teeth. This study was conducted at the UPTD Selemadeg Timur I Community Health Centre, Tabanan, Bali, from January to March 2025. This study was conducted using an observational cross-sectional method. Data on patient visits for persistent deciduous teeth at the Selemadeg Timur I Commu-nity Health Centre, involved 359 patients. It was concluded that the high incidence of persistent teeth at the health centre may be due to a lack of knowledge among parents.